Weber’s Ideal Type and the Indonesian Historical Writing - Akhyat, Arif (Paramita: Historical Studies Journal, 2022)
This paper explains subject–object relations in Max Weber's idealist-structural concept.  A sociologist and philosopher of history, Weber argued that social change cannot be separated from structural and dialectic thought as well as the ideal type behind its structural creations. Examining various historical cases offers a perspective on objectivity and subjectivity. Subject– object relations create dialectical relationships that reconstruct knowledge and awareness of historical reality. Historical reality, thus, is the final step in the creation of  knowledge that comes from the subject. The paper seeks to understand how Weber's concept of ideal type has influenced historical philosophy in general and Indonesian historiography in particular. This article concludes that historians no longer simply describe and explain facts, but also provide alternative "new constructions": ethical, moral, and superstructural values that determine historical patterns and trends.Tulisan ini menjelaskan relasi subjek-objek dalam konsep structural-idealisme Weber. Sebagai sosiolog dan filsuf sejarah, Weber berargumentasi bahwa perubahan social terjadi sebagai akibat hubungan struktur dan proses-proses dialektik sebagai bentuk idealisme dibalik semua proses social yang terjadi. Relasi subjektivitas dan objektivitas membentuk struktur dialektik yang kemudian memunculkan pengetahuan tentang apa yang disebut realitas sejarah. Realitas sejarah dengan demikian merupakan proses pengetahuan yang dibentuk dari relasi subjektivitas-objektivitas. Tulisan ini menjelaskan bagaimana konsep Ideal Weber itu dipahami dan pengaruhnya terhadap penulisan sejarah Indonesia? Hasil kajian ini menunjukkan bahwa sejarawan Indonesia, langsung atau tidak langsung, menggunakan konsep ideal Weber  dalam karyanya yang tidak hanya berbicara deskripsi dan narasi dalam menjelaskan sejarah, namun ada konstruksi baru pengaruh nilai-nilai, etika dan suprastruktur yang kuat dan menjadi cara menentukan pola dan kecendrungan sejarah.Cite this article: Akyat, A. (2022). Weber’s Ideal Type and the Indonesian Historical Writing. Paramita: Historical Studies Journal, 32(1), 86-96. http://dx.doi.org/10.15294/paramita.v32i1.32171